The non-NMDA antagonist CNQX prevents release of amino acids into the rat spinal cord dorsal horn evoked by sciatic nerve stimulation - Palečková, V; Paleček, Jiří; McAdoo, D.J; Willis, W.D (Neuroscience letters, 1992)
Basal extracellular concentrations of 9 amino acids (AAs: aspartate, Asp; glutamate, Glu; asparagine, Asn; serine, Ser; glycine, Gly; threonine, Thr; alanine, Ala; taurine, Tau; and glutamine, Gln) were determined in the spinal cord dorsal horn of anesthetized rats using microdialysis and HPLC techniques. The concentrations of all measured AAs but Gln increased significantly (P < 0.05) during sciatic nerve stimulation at C-fiber strength. The concentration of Tau remained elevated following stimulation, while the other AAs returned to prestimulation values. Addition of the specific non-NMDA antagonist, CNQX, to the perfusing solution prevented the nerve stimulation-evoked AA release. Since the measured increases in extracellular AA concentrations are probably mainly due to activation of interneurons, these results suggest that blockade of non-NMDA receptors prevented activation of interneurons in the dorsal horn and support a major role of non-NMDA receptors at the first synapse of primary afferent fibers in the dorsal horn. Complete block of AA release and decreased basal levels of Glu after infusion of TTX into the dorsal horn also implies increased neuronal activity as the main source of higher AA levels during nerve stimulation.
Keywords: Animals; Nerve Fibers; nervus ischiadicus; elektrická stimulace; potkani Sprague-Dawley; 6-kyano-7-nitrochinoxalin-2,3-dion; Receptors, N-Methyl-D-Aspartate; Sciatic Nerve; zvířata; receptory neurotransmiterů; tetrodotoxin; Rats, Sprague-Dawley; Spinal Cord; nervová vlákna; Rats; Male; 6-Cyano-7-nitroquinoxaline-2,3-dione; aminokyseliny; Quinoxalines; Amino Acids; Electric Stimulation; Tetrodotoxin; krysa rodu Rattus; receptory N-methyl-D-aspartátu; mícha; Receptors, Neurotransmitter; mužské pohlaví; chinoxaliny